Processed Multibeam Sonar Data (version 2) from the Amundsen Sea acquired during Nathaniel B. Palmer expedition NBP0702 (2007) (IEDA: Marine-Geo Digital Library, 2007)
This data set was acquired with a Kongsberg model EM120 multibeam sonar system during Nathaniel B. Palmer expedition NBP0702 conducted in 2007 (Chief Scientist: Dr. Stan Jacobs). These data files include Acoustic Backscatter, Sidescan, Swath Bathymetry data and were processed at sea using the open source MB-System multibeam sonar processing software. These data are included in the GMRT Synthesis, beginning with version 1. Data were acquired as part of the project(s): The Amundsen Continental Shelf and the Antarctic Ice Sheet, and funding was provided by the U.S. National Science Foundation.